Performance Analysis of Smart Stick Designed for Visually Impaired People Using GSM and GPS - Amutha Priya, N.; Sahaya Sathesh Raj, S.; Siva, K.; Vetha Jebarson, R.; Vignesh, P. (Asian Journal of Engineering and Applied Technology, 2021)
Visual impairment burdens the people heavily in today’s fast-moving culture. Although there are several measures for this impairment, many people skip such chances in fear of their economic condition. In view of helping those people, a sophisticated stick is designed using sensors like ultrasonic sensor, IR sensor and Arduino ICs. Electronically designed walking stick helps to trace the locations using GPS module and to avoid collisions through detection of objects at a certain range of distance from the person in all directions. Sensor placed beneath the bottom of the stick enables the identification of pits/hindrances on the ground. The visually impaired person will be alerted with a voice message generated using the voice recorder which records the response of all the sensors operating in different tracks. In this paper, GSM and sensors together have initiated the role of smart walking stick in the life of several human kinds.